Hubungan Tingkat Stres, Aktivitas Fisik dan Konsumsi Fast Food dengan Siklus Menstruasi Pada Mahasiswi Keperawatan Universitas Nasional Jakarta - Rita Dwi Yunianti; Cholisah Suralaga; Susanti Widiastuti (Malahayati Nursing Journal, 2024)
ABSTRACT Abnormalities in the menstrual cycle are indicative of an unstable metabolic and hormonal system, which can affect a woman's ability to conceive. Stress levels, physical activity, and fast food consumption are the causes of irregular menstrual cycles. Inadequate treatment for symptoms of irregular menstrual periods increases the risk of osteoporosis and iron deficiency anemia, and a reproductive disease called infiltrates. The purpose of this study is to ascertain how stress levels, physical activity levels, and fast food intake relate to menstrual periods among South Jakarta National University nursing students. Cross sectional methodology. The population is a regular class student of the 2021-2022 class of the National University of Jakarta Nursing program totaling 175 people. The sampling technique used Random Sampling with a total of 122 respondents. The research findings showed that there was a significant relationship between stress levels, physical activity, and fast food consumption related to menstrual cycles in nursing students of Universitas Nasional Jakarta, with p values of 0.000 0.05 for stress levels during the menstrual cycle. The p-values for fast food consumption and physical activity throughout the menstrual cycle were 0.000 0.05 and 0.000 0.05, respectively. The conclusion of this study is that the level of stress, physical activity, and fast food consumption among nursing students of the National University of Jakarta has a significant relationship with the menstrual cycle. Keywords: Menstrual Cycle, Stress Level, Physical Activity, Fast Food Consumption  ABSTRAK Kelainan pada siklus menstruasi merupakan indikasi sistem metabolisme dan hormonal yang tidak stabil, yang dapat mempengaruhi kemampuan wanita untuk hamil. Tingkat stres, aktivitas fisik, dan konsumsi fast food adalah penyebab siklus menstruasi yang tidak teratur. Pengobatan yang tidak memadai untuk gejala siklus menstruasi yang tidak teratur meningkatkan risiko osteoporosis dan anemia defisiensi besi, dan penyakit reproduksi yang disebut infiltrat. Tujuan dari penelitian ini adalah mengetahui bagaimana tingkat stres, tingkat aktivitas fisik, dan asupan makanan cepat saji berhubungan dengan periode menstruasi di kalangan mahasiswa keperawatan Universitas Nasional Jakarta Selatan. Metodelogi Cross Sectional. Populasinya adalah  mahasiswi kelas regular angkatan 2021-2022 prodi Keperawatan Universitas Nasional Jakarta berjumlah 175 orang. Teknik pengambilan sampel menggunakan Random Sampling dengan jumlah 122  responden. Temuan penelitian menunjukkan bahwa ada hubungan yang signifikan antara tingkat stres, aktivitas fisik, dan konsumsi fast food terkait dengan siklus menstruasi pada mahasiswi keperawatan Universitas Nasional Jakarta, dengan nilai p 0,000 0,05 untuk tingkat stres selama siklus menstruasi. Nilai p untuk konsumsi fast food dan aktivitas fisik sepanjang siklus menstruasi masing-masing adalah 0,000 0,05 dan 0,000 0,05. Kesimpulan penelitian ini bahwa tingkat stres, aktivitas fisik, dan konsumsi fast food pada mahasiswi keperawatan Universitas Nasional Jakarta terdapat hubungan yang signifikan dengan siklus menstruasi. Kata Kunci: Siklus Menstruasi, Tingkat Stres, Aktivitas Fisik, Konsumsi Fast Food